2014
DOI: 10.1111/apt.12651
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the declining risk of colorectal cancer in ulcerative colitis

Abstract: SUMMARY BackgroundPatients with ulcerative colitis (UC) have an increased risk of developing colorectal cancer (CRC); however, the magnitude of this effect is open to debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(136 citation statements)
references
References 125 publications
(410 reference statements)
4
127
4
1
Order By: Relevance
“…Likewise, the population-based Dutch cohort of UC patients diagnosed during 1991-2011 demonstrated a decreased risk of CRC in UC patients compared to that of the background population (SIR 0.45, 95% CI 0.19-0.88) [23] . Finally, a meta-analysis of both population-based and referral-centre studies showed a decreasing trend in CRC in UC patients according to the decade of the publication year [24] . The risk of CRC dropped from 4.29/1,000 person years disease duration (PYD) in studies published in 1950s to slightly over 1.20/1,000 PYD in publications at or after the year 2000.…”
Section: Ulcerative Colitismentioning
confidence: 97%
See 1 more Smart Citation
“…Likewise, the population-based Dutch cohort of UC patients diagnosed during 1991-2011 demonstrated a decreased risk of CRC in UC patients compared to that of the background population (SIR 0.45, 95% CI 0.19-0.88) [23] . Finally, a meta-analysis of both population-based and referral-centre studies showed a decreasing trend in CRC in UC patients according to the decade of the publication year [24] . The risk of CRC dropped from 4.29/1,000 person years disease duration (PYD) in studies published in 1950s to slightly over 1.20/1,000 PYD in publications at or after the year 2000.…”
Section: Ulcerative Colitismentioning
confidence: 97%
“…Risk factors of CRC include disease extension, young age at diagnosis, disease duration, positive family history of CRC and presence of primary sclerosing cholangitis (PSC) [20,21,24,25] . According to 2 meta-analyses of population-based studies, patients with extensive colitis had 4.8-and 6.9-fold increased risk of CRC than healthy population, while individuals with proctitis had the same risk as that of the background population [20,21] .…”
Section: Ulcerative Colitismentioning
confidence: 99%
“…The most recent meta-analysis of CRC, which was published in 2014, found that the overall risk of CRC in 181,923 UC patients was 1.69/1,000/year; this risk was 0.91/1,000/year in the first decade after the diagnosis of UC, 4.07/1,000/year in the second decade and 4.55/1,000/year in the third decade [1]. These rates are lower than those reported by a meta-analysis published in 2001 [2]: 3/1,000/year overall and 2, 8 and 18% in the first, second and third decades after diagnosis, respectively.…”
Section: Epidemiology Of Ibd-associated Crcmentioning
confidence: 99%
“…As mentioned above, two meta-analyses [1,2] from different time periods suggest that the incidence of IBD-associated CRC is in decline. A cohort study conducted in Denmark between 1962 and 1987 reported only 13 cases of CRC among 1,160 UC patients [24].…”
Section: Factors Protecting Against Ibd-associated Crcmentioning
confidence: 99%
“…The incidence of IBD-associated CRC is indeed decreasing over time as a likely consequence of the considerable efforts in recent decades directed at lowering CRC risk in patients with IBD [1]. Surveillance colonoscopy is often credited with this reduction, likely due to improvements at detecting and removing precancerous dysplastic lesions, particularly with the assistance of high definition and enhanced imaging technology.…”
mentioning
confidence: 99%